RESPOSTA DE ENRAIZAMENTO DE GENÓTIPOS CONTRASTANTES DE COFFEA CANEPHORA MEDIANTE USO DO AIB - Sallin, Valeria Pancieri (2022)
Sallin, Valéria Pancieri; MSc; Federal University of Espirito Santo; February 2022; Rooting response of contrasting genotypes of Coffea canephora using IBA; Advisor: Sara Dousseau Arantes; Co-advisor: Jean Marcel Sousa Lira. In the climate change scenario